1987
DOI: 10.1021/bi00390a026
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a subunit form of the light-harvesting complex of Rhodospirillum rubrum

Abstract: A new method is described for the isolation of subunits of the light-harvesting complex from Rhodospirillum rubrum (wild type and the G-9 mutant) in yields that approach 100%. The procedure involved treating membrane vesicles with ethylenediaminetetraacetic acid-Triton X-100 to remove components other than the light-harvesting complex and reaction center. In the preparation from wild-type cells, a benzene extraction was then employed to remove carotenoid and ubiquinone. The next step involved a careful additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
199
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(210 citation statements)
references
References 26 publications
11
199
0
Order By: Relevance
“…This agrees with the studies of Miller et al who found a stoichiometry of two for the BChl to R and polypeptides (13). For calculation of the association constants, we assumed that such a dimerization reaction is indeed leading to the formation of B820.…”
Section: Oligomerization Of B777 Into B820supporting
confidence: 89%
See 4 more Smart Citations
“…This agrees with the studies of Miller et al who found a stoichiometry of two for the BChl to R and polypeptides (13). For calculation of the association constants, we assumed that such a dimerization reaction is indeed leading to the formation of B820.…”
Section: Oligomerization Of B777 Into B820supporting
confidence: 89%
“…They observed a fast (within seconds) red shift of 820 nm toward 860 nm upon reassociation, followed by a slow final 12-15 nm shift, taking hours to days. Further, Miller et al measured spectra slightly blue-shifted from the B873 spectrum in the reassociation process (13). The forms absorbing around 860 nm are probably the intermediate spectra that we also observed.…”
Section: Origin Of Spectral Intermediatessupporting
confidence: 77%
See 3 more Smart Citations